Thriving Against the Odds: A Photovoice Study on Canadian College Students’ Mental Health and Resilience Strategies - Toledo, Estefania; Borak, Katherine (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2025)
This study examines the challenges and resilience of nine Canadian students enrolled in a Bachelor of Child and Youth Care (CYC) program at a polytechnic institution in Ontario, focusing on their mental health and well-being in post-secondary education. Using photovoice, students acted as co-researchers, sharing their lived experiences through visual and narrative expression. Participants revealed barriers such as limited access to mental health services, academic demands, and food insecurity. Despite these challenges, students demonstrated resilience through self-advocacy, physical activity, community connection, and relationships with the Land. Framed by French et al.’s (2020) theory of radical healing, the research calls for systemic change and highlights the shared responsibility of faculty, staff, and administrators to foster inclusive and culturally responsive supports. Findings emphasize the need for accessible student services and academic support, offering insights into how post-secondary institutions can better support students’ academic and holistic well-being.